Prevalence and associated factors of stress, anxiety and depression among trainee in Anaesthesiology department, University of Malaya / Siew Gee Ho - Siew, Gee Ho (2019)
Background In 2016, the data registry of American Association Of Medical Colleges (AMMC) found that there are 1103 doctors suicided. Anaesthesiologists have 5.5 times the rate of suicide of general internal medicine doctors. This study is to determine prevalence and associated factors of depression, anxiety and stress among anaesthesia trainees working at the department of aesthesiology Universiti of Malaya (UM). Method This study is a prospective, single centre, cross-sectional study that collects information on DASS–21 Score and a demographic data of anaesthesia trainee in University of Malaya. The inclusion criteria are anaesthesia trainees in Master program who are able to understand, read and speak Bahasa Malaysia language. Participant with psychosis, mental disability or refuse to participate were excluded from the study. 6 Result There is a total of 64 participant in this study. By using DASS-21 the prevalence among anaesthetist trainees in UM was anxiety (56.2%), followed by depression (39.1%) and stress (32.8%) (see Table 1). From Table 2, we noticed that the prevalence of depression was significantly associated with age (p = 0.044), regularity of physical exercise (p=0.029), number of on-call (p= 0.029) , duration to travel to UMMC from home (p=0.013) and poor memory (p=0.040). From Table 3, the prevalence of anxiety was associated with poor memory (p=0.012). In table 4, there is a significant association between age and stress (p=0.006). Conclusion Anaesthesia is playing an important role in all the surgery, intensive care, and pain management in the hospital. A 2009 survey showed that there were about 620 anaesthesiologists in the Malaysia, giving us a ratio of about one anaesthesiologist to 45,000 of the population. This is still far from the figures of developed countries of one in 10,000. The prevailing ratio of anaesthesiologists to surgeons in time is about one in four in Malaysia, as compared to one in two in developed countries. The prevalence of anxiety is high among anaesthetist trainees at Universiti of Malaya followed by depression and stress. Poor memory has been significantly associated with both depression and anxiety, whereas age is significantly associated with both depression and stress. Other factors that associated with depression were age, regularity of 7 exercise, and time spend on the travel to UMMC from home. This information could help to identify the group at risk and provide them support, guidance and advice in order to achieve work life balance.